High-performance flexible pentacene transistor memory with PTCDI-C13 as N-type buffer layer. (1st February 2023) - Wu, Lei; Yu, Tianpeng; Liu, Zhenliang; Wang, Yiru; Wan, ZuTeng; Yin, Jiang; Xia, Yidong; Liu, Zhiguo
Abstract: Flexible organic field-effect transistor nonvolatile memories (OFET-NVMs) with polymer electrets have aroused great attention for its important role in next-generation flexible data storage devices application. However, the OFET-NVMs to date still hardly reach the requirements for practical applications. In air environment, the positively charged defects formed in pentacene near the interface with polymer, result in unsatisfied high programming/erasing (P/E) voltages. Here, we propose an OFET memory structure, in which an n-type semiconductor N, N′-Bis(3-pentyl) perylene-3, 4, 9, 10-bis(dicarboximide) (PTCDI-C13 ) is inserted between pentacene and poly(4-vinyl phenol. Based on the electrostatic induction effect, electrons are induced on the surface of PTCDI-C13 due to the electrostatic field generated by the positive charges at the interface of pentacene/polymer, and compensate part of the positive charges at the interface, resulting in the reduction of the height of hole-barrier. The flexible memory device with PTCDI-C13 exhibits a memory window of larger than 7 V at P/E voltages (±20 V), fast switching speeds (0.5 ms), good P/E endurance (>400 cycles), large field-effect mobility (0.026 cm 2 V −1 s −1 ), and long retention time (over 10 4 s).